Antioxidant, antimicrobial and cytotoxic potential of silver nanoparticles synthesized using flavonoid rich alcoholic leaves extract of Reinwardtia indica - Upadhyay P.; Mishra S.K.; Purohit S.; Dubey G.P.; Singh Chauhan B.; Srikrishna S. (My University, 2025)
The present work discusses the establishment of a green route for the rapid synthesis of silver nanoparticles (AgNPs) using an alcoholic extract of Reinwardtia indica (AERI) leaves which act as a reducing as well as a capping agent. The change in color from yellowish green to dark brown confirmed the synthesis of AgNPs. A characteristic surface plasmon resonance (SPR) band at 436 nm advocated the presence of AgNPs. The synthesis process was optimized using one factor at a time approach where 1.0 mM AgNO 3 concentration, 5 mL 0.4% (v/v) of AER inoculum dose and 30 min of sunlight exposure were found to be the optimum conditions. The synthesized AgNPs was characterized by several characterizing techniques such as HR- TEM, SAED, HR-SEM, EDX, XRD, FTIR and AFM analysis. For evaluation and comparison of AgNPs with AERI used human pathogen E. coli, P. aeurogenosa, S. aeurus and C. albicans for antimicrobial, for cytotoxicity study SiHa cell line at concentration of (10, 50, 100, 250 and 500 µg mL −1 ) and for enzymatic assay superoxide dismutase, catalase, malondialdehyde and glutathione peroxidase method were used. The size of nanoparticle in the range of 3–15 nm was confirmed TEM, spherical shape by SEM and crystal lattice nature by XRD. AFM results revealed the 2 D and 3 D pattern of particle scatter nature on the surface. This protocol as simple, rapid, one step, eco-friendly, nontoxic and AgNPs showed strong antimicrobial activity as well as cytotoxic potential in comparison to AERI. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.